Model of the 2 × 25 kV high speed railway supply system taking into account the soil-air interface. (February 2018) - Minucci, Simone; Pagano, Mario; Proto, Daniela
Highlights: An accurate model of the High Speed Railway Supply System is proposed. The analysis of the traction supply system is based on the transmission lines theory. The presence of soil-air interface is considered. The proposed approach allows accurate evaluation of the system electrical quantities. The numerical simulations show the performances of the classical and new formulation. Abstract: This paper deals with the modelling of the 2 × 25 kV – 50 Hz high speed railway supply system. The proposed approach extends the traditional multi-conductor transmission line approach typically used for high speed railway systems, which is based on the assumption of overhead conductors. More specifically, this approach models the system by considering the presence of both overhead and buried conductors. Analytical formulations to calculate self and mutual line parameters are used. A numerical simulation allows evidencing the different results when the simplified and the detailed modelling approaches are adopted. A sensitivity analysis to point out the influence of the finitely conductive ground is also proposed.